REVOLUTIONIZING DRUG DELIVERY: THE ROLE OF SMART POLYMERS IN TARGETED THERAPEUTIC STRATEGIES - Mamatha H S, Ashok Kumar BS, Disha N S (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Smart polymers, also referred to as stimuli-responsive polymers, are a new class of materials that bring significant advancements in drug delivery systems (DDS). These polymers can respond to specific external stimuli, such as pH, temperature, light, enzymes, and magnetic fields, by changing their physical and chemical properties. This responsiveness allows for targeted and controlled drug delivery, minimizing systemic side effects and improving therapeutic efficacy. Smart polymers are versatile and can be applied in all therapeutic fields, such as cancer treatment, gene therapy, wound healing, and tissue engineering. Some of the latest innovations in DDS based on smart polymers include pH-sensitive polymers for targeted therapy of tumors, temperature-sensitive polymers for controlled drug delivery in febrile conditions, and light-responsive polymers for precise external control of drug delivery. Although promising, these materials face significant hurdles: stability, scalability, toxicity, biocompatibility, and regulatory approval to be used widely in the clinic. In addition, targeting specificity and high production costs limit their availability. Research and development are continuing to address these challenges, aiming to bring smart polymer-based DDS into routine clinical practice, thereby revolutionizing targeted therapies and personalized medicine. This review provides an overview of the types, mechanisms, innovations, and limitations of smart polymers in drug delivery, which would open up possibilities to transform modern therapeutic approaches.